Towards an artistic Account of Nature: Morphology, Hylology, Hylomorphism - Porceddu Cilione, Pier Alberto (Revista Archai, 2020)
A long philosophical tradition has claimed the fact that the concepts of physis and techne should remain radically distinct. But an equally important tradition has instead considered the question in less abstract terms. What can encourage us to rethink the question of hylomorphism is the radical rethinking of the terms at stake. How should the relationship between matter and form (two fundamental Aristotelian concepts) be thought? How should the distinction between natural form and artificial form be considered? The attempt that is proposed here is to consider art as the conceptual mediator that holds together a morphological determination of nature and a technical determination of art. ‘Artificiality’ should not be understood as the opposite of ‘naturalness’: art here means the possibility of thinking of techne already at work in nature, justifying the sense of a coming hylomorphism.